Hubungan Pengetahuan Ibu, Pendamping Persalinan, dan Massage Effleurage terhadap Penurunan Nyeri Persalinan Kala I di PMB Ruswanti, S.ST Cibeureum Bogor Tahun 2022 - Siti Rokhilah (SIMFISIS Jurnal Kebidanan Indonesia, 2023)
Introduction: Childbirth is a condition experienced by pregnant women throughout the world. Normal delivery (physiology) is the process in which the delivery of the fetus at term (37-42 weeks) and the placenta through the fetus is born spontaneously without any problems or complications. Labor is divided into 4 stages, namely stage I, stage II, stage III, and stage IV. The first stage is divided into 2 phases, namely the latent opening (1-3) and the active opening phase (4-10 complete). Objectives: This study aims to determine the relationship between knowledge of mothers, birth attendants, and massage effleurage on reducing pain in the first stage of labor at PMB Ruswanti., S.ST Bogor in 2022. Method: The type of research used in this research is descriptive-analytic with a cross-sectional approach. The data collection technique in this study is quantitative. The population used in this study were all mothers who gave birth at PMB Ruswanti, S.ST. The number of research samples is 44 respondents using the non-probability sampling method by accidental sampling. The research instrument used in this research was using a guttman scale questionnaire, bivariate analysis using Chi-Square. Result: The results of this study were 18 or (40.9%) respondents with a mild and moderate reduction in first-stage labor pain, 31 or (70.5%) respondents who had poor knowledge, 24 or (54.5%) respondents with birth attendants who well, 23 or (52.3%) had ever had an effleurage massage. the relationship between mother's knowledge and pain reduction, with a chi-square, p-value of 0.046, the relationship between childbirth assistance with a p-value of 0.001, and the relationship between massage effleurage with a p-value of 0.001 (p-value <0.05). Conclusion: In this study, there was a relationship between maternal knowledge and pain reduction, with a chi-square p-value of 0.046, there was a relationship between delivery assistance with a p-value of 0.001, and there was a relationship between massage effleurage with a p-value of 0.001 (p-value <0.05).